Promotion of National Interests and International Security as a Functional Focus of Diplomatic Service - Kuzmenko, O. V.; Gryhorenko, Ya. O. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2019)
the article attempts to determine the functions of the diplomatic service on the basis of a general theory of functions. A comparative analysis of individual principles and functions of the diplomatic service, which are regulated by the Law of Ukraine “On Diplomatic Service” of September 20, 2001 and the Law of Ukraine «On Diplomatic Service» of June 7, 2018, which comes into force on December 18, 2018, has been carried out. In general terms, issues of reforming the diplomatic service at the present stage of statehood development are outlined. The characteristic of ensuring national interests and international security as a functional guiding diplomatic service is presented.